Institutions are the main activity of a practicing psychologist directions (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article is one of the topical issues of today, and the scientific theoretical literature devoted to the study of the activity of the pedagogue in the management of the educational process is analyzed.